CD46 splice variant enhances translation of specific mRNAs linked to an aggressive tumor cell phenotype in bladder cancer - Zeng, Jin (Mol Ther Nucleic Acids, 2021)
CD46 is well known to be involved in diverse biological processes. Although several splice variants of CD46 have been identified, little is known about the contribution of alternative splicing to its tumorigenic functions. In this study, we found that exclusion of CD46 exon 13 is significantly increased in bladder cancer (BCa) samples. In BCa cell lines, enforced expression of CD46-CYT2 (exon 13-skipping isoform) promoted, and CD46-CYT1 (exon 13-containing isoform) attenuated, cell growth, migration, and tumorigenicity in a xenograft model. We also applied interaction proteomics to identify exhaustively the complexes containing the CYT1 or CYT2 domain in EJ-1 cells. 320 proteins were identified that interact with the CYT1 and/or CYT2 domain, and most of them are new interactors. Using an internal ribosome entry site (IRES)-dependent reporter system, we established that CD46 could regulate mRNA translation through an interaction with the translation machinery. We also identified heterogeneous nuclear ribonucleoprotein (hnRNP)A1 as a novel CYT2 binding partner, and this interaction facilitates the interaction of hnRNPA1 with IRES RNA to promote IRES-dependent translation of HIF1a and c-Myc. Strikingly, the splicing factor SRSF1 is highly correlated with CD46 exon 13 exclusion in clinical BCa samples. Taken together, our findings contribute to understanding the role of CD46 in BCa development.